Hubungan Tingkat Pendidikan Dan Dukungan KeluargaTerhadap Kepatuhan Diet Pada Pasien Gastritis Rawat InapDi Rsud Sukoharjo - Kusumaningrum, Novianti, Dwi Sarbini, SST (2017)
Background :Gastritis is an inflammation of the lining of the mucosa and submucosagaster or other complaints is stomach, nausea, vomiting, bloating, full flavor or burning in the upper abdomen. Diseases of gastritis if not handled properly it will cause complications such as peptic ulcer, impaired absorption of vitamin B12, and gastric cancer. Patients who run the diet should be obedient towards diets that are run if not obedient could hinder patients in the healing process. The level of education and family support is one of the factors which can affect diet compliance. Objective: This research aims to analyze the relationship of the level of education and family support against the patient's diet compliance gastritis in RSUD Sukoharjo. Methods: This type of research is conducted with servational approach of cross sectional. The subject of research as much as 24 patientsgatritis hospitalization in RSUD Sukoharjo. Data on the level of education and family support gained from charging the questionnaire. Diet compliance data can be seen from the form comstok (the rest of the patient's meal). Average test data using the Shapiro Wilk test and lationship with Rank Spearman test. Results: Gastritis patients have high levels of education as much as 50% and low levels of education as much as 50%. Most patients have a good family support of 79.2% and patients running diet dutifully as much as 62.5%. Test the correlation between the relationship between educational level and diet compliance shows the value of p = 0,106. Test the correlation between family support relationships and diet compliance shows the value of p = 0.901. Conclusion: There is no relationship between the level of education and family support diet compliance in patients against gastritis.